2017
DOI: 10.1111/adb.12485
|View full text |Cite
|
Sign up to set email alerts
|

Netrin G1: its downregulation in the nucleus accumbens of cocaine‐conditioned mice and genetic association in human cocaine dependence

Abstract: Netrin G1 is a presynaptic ligand involved in axonal projection. Although molecular mechanisms underlying cocaine addiction are still poorly understood, Netrin G1 might have a role as a regulator of anxiety, fear and spatial memory, behavioural traits impaired in the context of cocaine exposure. In this study, the Netrin G1 (Ntng1) expression was investigated in the nucleus accumbens of mice primarily conditioned to cocaine using a place preference paradigm. A genetic association study was then conducted on 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Together with previous results, this study highlights PLCB1 as a gene that may contribute to drug dependence. Finally, these findings and previous results from our and other groups on NFAT5 and NTNG1 11,12 suggest that genes which expression is altered by the effect of drugs of abuse may play an important role in the susceptibility to drug dependence.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Together with previous results, this study highlights PLCB1 as a gene that may contribute to drug dependence. Finally, these findings and previous results from our and other groups on NFAT5 and NTNG1 11,12 suggest that genes which expression is altered by the effect of drugs of abuse may play an important role in the susceptibility to drug dependence.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies had reported that two genes (NFAT5 and NTNG1) with altered expression under cocaine also bear variants that confer susceptibility to cocaine dependence as shown by association studies 11,12 . Since we have shown that PLCB1 is involved in the vulnerability to cocaine dependence, we explored the possibility that its expression is altered by the action of cocaine.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, three of the genes encoding differentially expressed mature miRNAs (hsa-miR-9-1, hsa-miR-153-1 and hsa-miR-124-3) were found to be nominally associated with cocaine dependence in this study. Previous studies had reported genes which expression is altered by cocaine and that also carry risk variants for cocaine dependence, or viceversa ( NFAT5, PLCB1 and NTNG1 ) 27 , 62 , 63 . The findings in the present study, together with the previous ones, support the hypothesis that genes up-regulated or down-regulated by cocaine may also contribute to the susceptibility to cocaine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of alcohol on netrins in the CNS has yet to be thoroughly investigated. However, a recent study of cocaine dependency in a young adult male mouse (18-20 g) model (induced by daily intraperitoneal injections of cocaine [15 mg/kg]) revealed the downregulation of netrins and the impairment of netrin1-dependent axonal guidance signaling [37], thus disrupting the formation of synapses. A subsequent study using human brain samples from 34 to 54 year-old adults also showed downregulation of netrins in response to cocaine dependency [37].…”
Section: Netrinsmentioning
confidence: 99%
“…However, a recent study of cocaine dependency in a young adult male mouse (18-20 g) model (induced by daily intraperitoneal injections of cocaine [15 mg/kg]) revealed the downregulation of netrins and the impairment of netrin1-dependent axonal guidance signaling [37], thus disrupting the formation of synapses. A subsequent study using human brain samples from 34 to 54 year-old adults also showed downregulation of netrins in response to cocaine dependency [37]. In developmental rodent studies, loss-of-function or mutations of netrin1 or its receptors produced pups with impaired motor function; these pups would not suckle and died within a few days [32,38].…”
Section: Netrinsmentioning
confidence: 99%